Surgical curettage associated with cryotherapy as an alternative for the treatment of odontogenic maxillary myxoma: Report of a clinical case (Research, Society and Development, 2021)
Odontogenic myxoma is a benign tumor, representing 3 a 5% of odontogenic tumors of ectomesenchymal origin. It has high rates on recurrence, mainly for treating a nonencapsulated tumor. Usually accompanies Young adult, around 30 years old, with a slight predilection for the female sex. Asymptomatic in its initial phase, but larger lesions can cause dental detachment or mobility, dysesthesias and ulcerations. It presents radiografhically as a radiological lesion, indefinite limits, and there may be boné beamns inside (“soap bubble” aspect). There is no protocol for the treatment of tumors, since it can be presented in the mandible and maxilla. Some literature relates to more conservative treatment such as curgical curettage associated cryoterapy, to maintain the patient’s function and aesthetics. The present work aims the clinical case of patient female, 38 years, who exhibits the Odontogenic Myxoma at the maximum diagnosis in 1997, with the treatment of surgical curettage associated cryoterapy being carried out, with monitoring of 23 years in which a patient does not present significant bone defector dental absences, wear and tear of the maintenance of function and facial aesthetics.